Anti-Social Behavior in Groups - Michal Bauer; Jana Cahlíková; Dagmara Celik Katreniak; Julie Chytilová; Lubomir Cingl; Tomáš Želinský (Institute of Labor Economics (IZA), 2018)
This paper provides strong evidence supporting the long-standing speculation that decision-making in groups has a dark side, by magnifying the prevalence of anti-social behavior towards outsiders. A large-scale experiment implemented in Slovakia and Uganda (N=2,309) reveals that deciding in a group with randomly assigned peers increases the prevalence of anti-social behavior that reduces everyone's payoff but which improves the relative position of own group. The effects are driven by the influence of a group context on individual behavior, rather than by group deliberation. The observed patterns are strikingly similar on both continents.
Keywords: C92; C93; D01; D64; D74; D91; 330; group decision-making; antisocial behavior; aggressive competitiveness; group membership; group conflict